Nurses’ Barriers to Incident Reporting in Patient Safety Culture: A Literature Review - Diah Arruum; Enie Novieastari (Indonesian Journal of Global Health Research, 2020)
Patient safety culture becomes the responsibility of every health care provider, but there are still barriers to reduce adverse events, and one of them is due to the barriers to incident reporting. This study obtained and used the databases from ProQuest, Science Direct, SAGE Publications, and EBSCOhost. The inclusion criteria were nurses and other health care providers as the sample population, barriers, factors, reporting, patient safety culture, adverse events, nurses' perception, implication, and experience. Four electronic databases were searched for data from 2016 to 2020 with English guidelines and full-text search assessed for the inclusion criteria. Fourteen articles fulfilled the inclusion criteria. The study found various barrier factors in incident reporting, including psychological problems and emotional reactions, such as shame, guilt, fatigue due to overwork, patient-nurse ratio, increased workload, insufficient time to respond the patients, lack of professionalism, medication errors, lack of resources and staff, and lack of feedback for error reporting. Personal and professional support for nurses or other health care providers is required to encourage error reporting without feeling guilty and ashamed to colleagues or feeling fearful of the supervisor in order to obtain more accurate data and improve the process that support patient safety and nurses’ self-awareness.